The Influence of the Covid - 19 Pandemic and Government Policy on Hotel Room Occupancy Rates - Yuwantiningrum, Sri Endah (Prodi Pariwisata dan LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
The Covid-19 pandemic has dealt a heavy blow to the tourism sector. Restrictions on travel and in-person meetings have caused the transportation and lodging accommodation sector to drop drastically. Several policies, regulations and requirements for traveling are also obstacles for the hotel industry to be able to receive guests. An increase in the number of Covid-19 sufferers in an area will be followed by restrictions on travel regulations and policies, which will not only impact the local community, but also other residents who want to come or cross the area. These conditions directly affect the occupancy rate of hotel rooms in an area. This study used a secondary research method based on existing data. Sources of data come from daily and weekly reports on the occupancy rate of hotel rooms in the city of Bogor, as well as data obtained from other sources. The purpose of this study is to serve as a dashboard for future policy makers, especially on the impact of a policy on the occupancy rate of hotel rooms. Keywords: Pandemic, Room Occupancy Rate, Government Policy